2016
DOI: 10.1007/s00402-016-2499-4
|View full text |Cite
|
Sign up to set email alerts
|

Two-staged application of PRP in arthroscopic rotator cuff repair: a matched-pair analysis

Abstract: Level III, Retrospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…16,33,69 However, other published studies often employed a single (or multiple) PRP injection at, or into, the repair site at the time of surgery. †† Gwinner et al 37 employed multiple PRP injections at the repair site as well as into the subacromial bursa at the time of surgery, with a second injection at 7 days after surgery into the subacromial bursa. Hak et al 38 injected into the tendon intraoperatively in several positions along the repair site as well as into the subacromial bursa, with a second series of injections at the tendon-bone interface and into the subacromial bursa at 4 weeks after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,33,69 However, other published studies often employed a single (or multiple) PRP injection at, or into, the repair site at the time of surgery. †† Gwinner et al 37 employed multiple PRP injections at the repair site as well as into the subacromial bursa at the time of surgery, with a second injection at 7 days after surgery into the subacromial bursa. Hak et al 38 injected into the tendon intraoperatively in several positions along the repair site as well as into the subacromial bursa, with a second series of injections at the tendon-bone interface and into the subacromial bursa at 4 weeks after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The postoperative improvement observed in the QuickDASH and OSS in this study appears consistent with the existing literature evaluating outcomes after rotator cuff repair in combination with PRP. 25 However, it must be acknowledged that a range of other PROMs have been employed in these studies, including the American Shoulder and Elbow Surgeons (ASES) questionnaire, 3,25,41,43,52,55 the Simple Shoulder Test (SST), 3,12,34,43,44,53,67,68 the subjective shoulder value (SSV), 37 the University of California, Los Angeles (UCLA) score, 12,43,44,49,52,53,56,67 the Shoulder Pain and Disability Index (SPADI), 43,44 the Western Ontario Rotator Cuff Index (WORC), 37,41 and the L'Insalata shoulder score. 55 The use of different PROMs makes a direct comparison difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggested a pain reduction following PRP application [ 16 , 44 ]. However, recent reviews and meta-analyses found no significant effects of PRP augmentation in the treatment of full thickness RC tear repairs by means of outcome scores or re-tear rates [ 5 , 7 , 21 , 30 , 47 , 51 , 60 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…As well as, there are new technologies are used in PRP preparation by using ACP system (autologous conditioned plasma) [33], AutoloGel™ system for PRP diabetic ulcer treatment and commercially available kits [34]. Although these methods are recently available techniques; the classical centrifugal method was described as low cost preparation method, most accurate and rational choice for manual making [35,36].…”
Section: Discussionmentioning
confidence: 99%